2013
DOI: 10.3109/0142159x.2013.774334
|View full text |Cite
|
Sign up to set email alerts
|

Transforming health professional education through social accountability: Canada's Northern Ontario School of Medicine

Abstract: There are signs that NOSM is successful in graduating health professionals who have the skills and desire to practice in rural/remote communities and that NOSM is having a largely positive socioeconomic impact on Northern Ontario.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 12 publications
2
88
0
3
Order By: Relevance
“…A chapter in the recently published international Rural Medical Education Guidebook highlights some of the complexities and challenges that need to be considered in looking at this issue. [17] It should be noted that the Northern Ontario School of Medicine has demonstrated that its distributed rural medical education programme has had a substantial positive socioeconomic impact on local communities. [18] Implications for SA The international literature reveals the complexity and intensity of successful rural programmes.…”
Section: Challenges Faced By Rural Programmesmentioning
confidence: 99%
“…A chapter in the recently published international Rural Medical Education Guidebook highlights some of the complexities and challenges that need to be considered in looking at this issue. [17] It should be noted that the Northern Ontario School of Medicine has demonstrated that its distributed rural medical education programme has had a substantial positive socioeconomic impact on local communities. [18] Implications for SA The international literature reveals the complexity and intensity of successful rural programmes.…”
Section: Challenges Faced By Rural Programmesmentioning
confidence: 99%
“…This ambition was embedded in a medical curriculum created by the visionary leadership of the founding dean Peter F. Hjort (1924Hjort ( -2011, (Medical curriculumTromsø 1971). A major innovation was that students should train nearly a year outside campus engaged with rural general practices and local hospitals all over Northern Norway (Nordøy 1985;Fønnebø Knutsen et al 1986;Aaraas & Halvorsen 2014 ).This constituted a socially accountable profile of the Tromsø programme, which has been internationally acknowledged, and developed into innovative and comprehensive models across the world (Rabinowitz et al 2005;Norris et al 2006;Strasser et al 2013;Sen Gupta et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The authors describe a shift from the goal of knowledge and professional credentials acquisition to a model of competency-driven, interdependent, team-based community health with the needs of the population at the core [2]. Grounding education in social accountability and community [38] also upholds the business principle of "design thinking" that starts with listening to, and empathy for, recipients of innovation [39]. In this section, we outline two educational principles that begin with learners, patients, and populations as the primary drivers of educational design.…”
Section: Guiding Educational Principlesmentioning
confidence: 99%
“…Benefits of the program are clear and reaching, with increased economic activity, a larger school budget, and increased recruitment and retention of a diverse healthcare workforce [57]. Perhaps most critically, there is also a growing sense of empowerment among community participants and development of "community capacity and opportunities for innovation and growth [38]. "…”
Section: Lics-restructuring Education For Workforce Transformationmentioning
confidence: 99%